Transition markers in argumentative texts of native speakers and foreign language learners: comparison of Croatian as L1 and German as L2 - Bagarić Medve, Vesna; Karlak, Manuela (Slavia Centralis, 2023)
Transition markers (TMs) help the reader to interpret pragmatic connections between the individual steps of an argument. From this function emerges the importance of these metadiscursive elements in argumentative writing. In the present corpus linguistic study, the use of TMs in L1 Croatian and L2 German texts written by university students of German studies (B2 language level in German) is analysed. A comparison of the frequency of use of TMs overall and the three subcategories of TMs (addition, comparison and consequence) in the L1 and L2 texts showed a statistically significant difference only for the use of TMs of comparison. However, the results suggest a less varied use of TMs in L2 texts and the potential transfer of these linguistic structures from the L1 to the L2.